Mujeres en la Colonia. Dominación colonial, diferencias étnicas y de género en cofradías y fiestas religiosas en Jujuy, Río de la Plata - Normando Cruz, Enrique (Pontificia Universidad Católica del Perú. Fondo Editorial, 2005)
The article makes a comparative analysis of the participation of women in the fraternities and religious celebrations, and reveals that at the end of the colonial period there exists «distance between them» established by the economic, cultural and ethnical differences (Bourdieu 2000: 116), between the indigenous women of the rural world and the Spanish women of the elite and between the half-breed and Indian women of the urban shell. This study allows us to see that, while the voices of the female indigenous peasants of Purmamarca, Tumbaya or Cholacor enjoy themselves freely—and sometimes with the use of alcohol—in public spaces, where they work together with the men, and sing with periodical authority in the everyday life of the religious celebrations; the voices of the peasants of the cooperative and the indigenous women who make chicha in the San Salvador de Jujuy square are almost always dominated by a man, can pray their litany only in the chorus of the religious brotherhoods, in family life or in public work spaces which are authorized and controlled by men.

El artículo analiza comparativamente la participación de las mujeres en las cofradías y las fiestas religiosas. Revela que a fines del periodo colonial, las mujeres indígenas del mundo rural son distintas a las mujeres españolas de la élite y a las mujeres mestizas e indias del casco urbano, pues existe entre ellas una «distancia entre sí», establecida no solo por las diferencias económicas y culturales (Bourdieu 200: 116), sino también por las diferencias étnicas. Las voces de las campesinas indígenas de Purmamarca, Tumbaya o Cholacor se regodean en libertad, y a veces alcoholizadas, en los espacios públicos del trabajo junto a los hombres, y cantan con autoridad periódica en la cotidianeidad de las fiestas religiosas. En cambio, las campesinas del ejido y las chicheras indígenas que trabajan en la plaza de San Salvador de Jujuy solo pueden alzar su letanía en los coros de las cofradías religiosas, en la vida familiar o en el trabajo en espacios públicos, lugares también habilitados y controlados por el hombre.
Women in the Colony. Colonial domination, ethnic and gender differences in cofradías and religious festivals in Jujuy, Río de la Plata
Keywords: Género; Colonia; Cofradías; https://purl.org/pe-repo/ocde/ford#5.04.03